Environmental Association Identifies Candidates for Tolerance to Low Temperature and Drought. Issue 10 (1st October 2019) - Lei, Li; Poets, Ana M; Liu, Chaochih; Wyant, Skylar R; Hoffman, Paul J; Carter, Corey K; Shaw, Brian G; Li, Xin; Muehlbauer, Gary J; Katagiri, Fumiaki; Morrell, Peter L
Abstract: Barley ( Hordeum vulgare ssp. vulgare ) is cultivated from the equator to the Arctic Circle. The wild progenitor species, Hordeum vulgare ssp. spontaneum, occupies a relatively narrow latitudinal range (∼30 - 40° N) primarily at low elevation (< 1, 500 m). Adaptation to the range of cultivation has occurred over ∼8, 000 years. The genetic basis of adaptation is amenable to study through environmental association. An advantage of environmental association in a well-characterized crop is that many loci that contribute to climatic adaptation and abiotic stress tolerance have already been identified. This provides the opportunity to determine if environmental association approaches effectively identify these loci of large effect. Using published genotyping from 7, 864 SNPs in 803 barley landraces, we examined allele frequency differentiation across multiple partitions of the data and mixed model associations relative to bioclimatic variables. Using newly generated resequencing data from a subset of these landraces, we tested for linkage disequilibrium (LD) between SNPs queried in genotyping and SNPs in neighboring loci. Six loci previously reported to contribute to adaptive differences in flowering time and abiotic stress in barley and six loci previously identified in other plant species were identified in our analyses. In many cases, patterns of LD are consistent with the causative variant occurring in the immediate vicinity of the queried SNP. The identification of barley orthologs to well-characterized genes may provide a new understanding of the nature of adaptive variation and could permit a more targeted use of potentially adaptive variants in barley breeding and germplasm improvement.